DELIRIUM PADA PASIEN RAWAT INAP DENGAN SKIZOFRENIA: SEBUAH LAPORAN KASUS - Made Ayu Dwi Pradnyawati; Nyoman Ratep; Wayan Westa (Universitas Udayana, 2014)
Delirium is psychiatric disorder characterized by conciousness state impairment,disorientation, and affective alteration, including cognitive and non-cognitive deficite, anddeveloped in acute onset. Delirium stand in organic mental disorder group, which has manysimilarity of signs and symptoms with psycotic mental disorder as schizophrenia. Delirium,particularly that is not related with alcohol and drug abuse, frequently found in elderly. Somecases of delirium among inpatient psychiatric patients have been reported, but just few furtherstudies have been held on those cases. This case report try to deliver a case of delirium in a65 y.o. inpatient paranoid type schizophrenia. This patient showed sign of severedisorientation during his treatment. In psychiatric assesment, stated male patient withinappropriate appearance, contact avoidance, decrease of conciousness, and severedisorientation. Mood/affect found irritable/appropriate. Patient experienced delution andhallucination. He suspected with undetected dementia as underlying disease.